Students' Perceptions on the Development of the ZEP Quiz as an Innovative Formative Assessment Tool in the “Grammar for TOEFL” Course - Wiji Kholifah; Yenni Rozimela; Syahrul R (Darul Yasin Al Sys, 2026)
Mastery of grammar is a crucial component of students’ success on the Test of English as a Foreign Language (TOEFL); however, grammar assessment that is still largely conducted through conventional methods may increase anxiety and reduce student engagement. ZEP Quiz, a metaverse-based assessment platform, integrates gamification, virtual avatars, competition, and immediate feedback into the evaluation process. This study aims to investigate students’ perceptions of using ZEP Quiz as an innovative formative assessment tool in the Grammar for TOEFL course. A descriptive quantitative survey design was employed, involving 30 students from the English Language Education Program at Padang State University. Data were collected using a 30-item questionnaire based on a four-point Likert scale and analyzed using descriptive statistics. The findings indicate that students demonstrated a very positive perception of ZEP Quiz, with a grand mean score of 3.36. The enjoyment dimension received the highest score (M = 3.50), followed by motivation (M = 3.39) and overall perception (M = 3.38). These findings suggest that ZEP Quiz can enhance students’ enjoyment and motivation in grammar assessment by providing an interactive, gamified, and feedback-oriented learning environment. This study concludes that ZEP Quiz has the potential to serve as an innovative formative assessment alternative for supporting Grammar for TOEFL learning in higher education. The findings contribute to the development of technology-enhanced language assessment and provide practical implications for lecturers in designing more engaging, interactive, and student-centered grammar assessment practices.